“An Analysis on Impact of Workplace Environment And Employees Involvement in Productivity At G.P.P.L. (Caplon), Surat” - , V Patel., Mr.Tanmay (International Journal of Scientific Research and Management (IJSRM), 2014)
“An Analysis on Impact of Workplace Environment And Employees Involvement in Productivity At G.P.P.L. (Caplon), Surat”